Design and operation of double hull tankers, London, UK, 25-26 February 2004 - International Conference on Design & Operation of Double Hull Tankers (2004 : London, UK); The Royal Institution of Naval Architects (Upper Belgrave Street, London : RINA, 2004)
Developing the next generation of classification rules for oil tankers -- Double hull & corrosion -- A risk-based design methodology for pollution prevention & control -- Proactive, risk-based structural integrity management of VLCC's based on FSA methods & safety case principals -- The performance, safety & production benefits of SPS structures for double hull tankers -- Low cost alternative for OPA 90: the articulated tug barge -- The double acting ship concept -- Operation experience with double hull tankers -- The double hull experience of USNS Patuxent -- Structural experience with double hull tankers -- Double-hulling: a viable alternative? -- Some recent experience with double hull tankers -- How to get the most from your inspections -- The use of advanced ultrasonic techniques for use in the inspection of double hull tankers -- Microbial growth & corrosion: what's so special about double hull tankers -- Restriction of corrosionin double hull ballast spaces.